2022
DOI: 10.3389/fphys.2022.857555
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High-Volume Versus High-Load Resistance Training on Skeletal Muscle Growth and Molecular Adaptations

Abstract: We evaluated the effects of higher-load (HL) versus (lower-load) higher-volume (HV) resistance training on skeletal muscle hypertrophy, strength, and muscle-level molecular adaptations. Trained men (n = 15, age: 23 ± 3 years; training experience: 7 ± 3 years) performed unilateral lower-body training for 6 weeks (3× weekly), where single legs were randomly assigned to HV and HL paradigms. Vastus lateralis (VL) biopsies were obtained prior to study initiation (PRE) as well as 3 days (POST) and 10 days following … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

6
3

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 59 publications
1
14
0
Order By: Relevance
“…Resistance training increases myofiber hypertrophy, whole-tissue hypertrophy, and strength [1]. Training with higher loads (e.g., ~80%+ of a person's one repetition maximum, or 1RM) and lower volumes (e.g., ~8-12 repetitions per set) generally increases force production capabilities versus lower load training with higher volumes (e.g., 20+ repetitions per set with 30-60% 1RM) [2][3][4][5], although equivocal evidence exists [6,7]. Notwithstanding, most studies to date support that a wide range of loads ≥30 1RM can promote a similar magnitude of skeletal muscle hypertrophy if training is performed to failure [5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Resistance training increases myofiber hypertrophy, whole-tissue hypertrophy, and strength [1]. Training with higher loads (e.g., ~80%+ of a person's one repetition maximum, or 1RM) and lower volumes (e.g., ~8-12 repetitions per set) generally increases force production capabilities versus lower load training with higher volumes (e.g., 20+ repetitions per set with 30-60% 1RM) [2][3][4][5], although equivocal evidence exists [6,7]. Notwithstanding, most studies to date support that a wide range of loads ≥30 1RM can promote a similar magnitude of skeletal muscle hypertrophy if training is performed to failure [5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…In a separate cohort of previously trained men, Vann et al [16] reported that a 10-week higher load and moderate-to-low volume training program did not alter the sarcoplasmic proteome or promote the glycolytic protein adaptations observed by Haun and colleagues. Vann et al [4] subsequently examined how six weeks of unilateral lower load versus higher load unilateral leg resistance training affected select molecular outcomes in a third cohort of previously trained men. While shotgun proteomics were not performed, these authors reported that six-week integrated non-myofibrillar protein synthesis rates were significantly greater in the lower load versus higher load trained leg.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that bodyweight squat can progress and enhance training intensity by increasing repetitions (13). However, under such progressive strategy (increase repetitions under a xed load), both untrained and trained people may not be very effective in improving the maximum strength (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, an increase in myofibrillar number, but not size, has been shown to accompanies the increases in fCSA with weeks of resistance training ( Jorgenson et al, 2023 ). However, select evidence suggests that non-myofibrillar area expansion may predominate during muscle fiber hypertrophy in resistance training protocols that diverge from traditional methods (e.g., an unconventional or very high-volume training paradigms) ( Haun et al, 2019 ; Fox et al, 2021 ; Vann et al, 2022 ). Despite extensive research into these intracellular changes in recent years, little is known regarding how LL-BFR affects these features in muscle fibers.…”
Section: Introductionmentioning
confidence: 99%